Baseline and longitudinal plasma caveolin‐1 level as a biomarker in active surveillance for early‐stage prostate cancer. (16th August 2017) - Basourakos, Spyridon P.; Davis, John W.; Chapin, Brian F.; Ward, John F.; Pettaway, Curtis A.; Pisters, Louis L.; Navai, Neema; Achim, Mary F.; Wang, Xuemei; Chen, Hsiang‐Chun; Choi, Seungtaek; Kuban, Deborah; et al.
Abstract : Objectives: To evaluate the role of caveolin‐1 (Cav‐1) as a predictor of disease reclassification (DR) in men with early prostate cancer undergoing active surveillance (AS). Patients and Methods: We analysed archived plasma samples prospectively collected from patients with early prostate cancer in a single‐institution AS study. Of 825 patients enrolled, 542 had ≥1 year of follow‐up. Baseline and longitudinal plasma Cav‐1 levels were measured using an enzyme‐linked immunosorbent assay. Tumour volume or Gleason grade increases were criteria for DR. Logistic regression analyses were used to assess associations between clinicopathological characteristics and reclassification risk. Results: In 542 patients, 480 (88.6%) had stage cT1c disease, 542 (100.0%) had a median prostate‐specific antigen level of 4.1 ng/mL, and 531 (98.0%) had a median Cancer of the Prostate Risk Assessment score of 1. In all, 473 (87.3%) had a Gleason score of 3+3. After a median of 3.1 years of follow‐up, disease was reclassified in 163 patients (30.1%). The mean baseline Cav‐1 level was 2.2 ± 8.5 ng/mL and the median 0.2 ng/mL (range, 0–85.5 ng/mL). In univariate analysis, baseline Cav‐1 was a significant predictor for risk of DR (odds ratio [OR] 1.82, 95% confidence interval [CI] 1.24–2.65; P = 0.002). In multivariate analysis, with adjustments for age, tumour length, group risk stratification and number of positive cores, reclassification risk associated with Cav‐1 remained significant (OR 1.91, 95% CI 1.28–2.84; P = 0.001). Conclusion: Baseline plasma Cav‐1 level was an independent predictor of disease classification. New methods for refining AS and intervention may result.